KARAKTERISTIK PETANI DAN KELAYAKAN USAHATANI NENAS MORIS DI KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Oni Ekalinda (Indonesian Journal of Agricultural Economics, 2017)
This study aimed to investigate the characteristics of farmers and moris pineapple farming costs, farmers' income, and eligibility of moris pineapple farming. The study used survey method with the number of respondents of 25 farmers. The study was conducted in Sukajadi Village, Kuala Cinaku sub-district, Indragiri Hulu, 2015. The qualitative data was analyzed descriptively while farm viability was analyzed using the balance of benefit cost ratio (BCR), the breakeven point of production and prices as well as sensitivity analyses. The results showed that more than 80% of farmers belong to the productive age with a similar level of primary school education as much as 66% with moris pineapple farming experience less than 10 years, or about 85% of the respondents. Total costs incurred for pineapple farming per hectare per cropping period is IDR 7.403 million. Gross revenues of morris pineapple farmers in the first year is IDR 9.765 million, the second year is IDR 13,662,500 and the third year is IDR 9.853 million. Economically, moris pineapple farming is not feasible with the BCR value of 0,78. A sensitivity analysis of farm use scenarios of increased production costs by 20% gained change of revenue of IDR 25,895,080 with the value of BCR of 2.9. While using scenarios to forego revenues by 20%, increase the cost of production by 20%, then there is a change in revenue of IDR 20,716,064 with the BCR value of 2.3.